4-1BB: A promising target for cancer immunotherapy - Kim, Alyssa Min Jung; Nemeth, Macy Rose; Lim, Seung-Oe (Frontiers in Oncology, 2022)
Immunotherapy, powered by its relative efficacy and safety, has become a prominent therapeutic strategy utilized in the treatment of a wide range of diseases, including cancer. Within this class of therapeutics, there is a variety of drug types such as immune checkpoint blockade therapies, vaccines, and T cell transfer therapies that serve the purpose of harnessing the body’s immune system to combat disease. Of these different types, immune checkpoint blockades that target coinhibitory receptors, which dampen the body’s immune response, have been widely studied and established in clinic. In contrast, however, there remains room for the development and improvement of therapeutics that target costimulatory receptors and enhance the immune response against tumors, one of which being the 4-1BB (CD137/TNFRSF9/ILA) receptor. 4-1BB has been garnering attention as a promising therapeutic target in the setting of cancer, amongst other diseases, due to its broad expression profile and ability to stimulate various signaling pathways involved in the generation of a potent immune response. Since its discovery and demonstration of potential as a clinical target, major progress has been made in the knowledge of 4-1BB and the development of clinical therapeutics that target it. Thus, we seek to summarize and provide a comprehensive update and outlook on those advancements in the context of cancer and immunotherapy.